APRESENTAÇÃO. - Marques, Diogo; Miguelote, Carla (eLyra: Revista da Rede Internacional Lyracompoetics, 2025)
The article presents the eLyra issue titled "Poetic Instructions: Ways to Use," which seeks to create a space for interaction between poetry and programming discourses, according to Greimas's definition. The dossier is structured as an open manual, where essays and poems intertwine, proposing a reading experience that challenges the passivity of the reader and invites experimentation. The texts address various forms of poetry, including visual and digital, and explore poetic language as a means of action and reflection on contemporary production. The reader is encouraged to move with curiosity, embracing uncertainty and the multiplicity of interpretations throughout the creative process.